2021
DOI: 10.3390/jcm10081762
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, Predictors, and Prognostic Value of Skeletal Muscle Mass Loss in Patients with Locally Advanced Head and Neck Cancer Undergoing Cisplatin-Based Chemoradiotherapy

Abstract: Low skeletal muscle mass (SMM) is associated with toxicities and decreased survival in head and neck cancer (HNC). Chemoradiotherapy (CRT) may exaggerate loss of SMM. We investigated the changes in SMM, their predictors, and prognostic impact of SMM in patients treated with CRT between 2012 and 2018. Skeletal muscle area (SMA) segmentation was performed on pre- and post-CRT imaging. Observed changes in SMM were categorized into: (I) Stable, (II) moderate gain (III), moderate loss, (IV) large gain, and (V) larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Furthermore, the FFMI of our patients also did not correlate with sex, PS, primary tumor location, overall disease stage, or type of treatment (definitive or postoperative (chemo)radiotherapy). This also contradicts the findings of some other authors, i.e., the relationship between low muscle mass and female sex [ 15 , 38 , 39 ] or higher overall disease stage [ 14 , 38 ]. However, we observed an association between reduction of muscle mass and smoking, as did Bril et al [ 38 ] but not also Wendrich et al [ 15 ] and Huiskamp et al [ 40 ], possibly reflecting the problem of the reliability of data obtained from patients.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the FFMI of our patients also did not correlate with sex, PS, primary tumor location, overall disease stage, or type of treatment (definitive or postoperative (chemo)radiotherapy). This also contradicts the findings of some other authors, i.e., the relationship between low muscle mass and female sex [ 15 , 38 , 39 ] or higher overall disease stage [ 14 , 38 ]. However, we observed an association between reduction of muscle mass and smoking, as did Bril et al [ 38 ] but not also Wendrich et al [ 15 ] and Huiskamp et al [ 40 ], possibly reflecting the problem of the reliability of data obtained from patients.…”
Section: Discussioncontrasting
confidence: 94%
“…An additional, albeit related, reason was the high prevalence of low muscle mass (56.3%) in our patients, which turned out to be an independent adverse prognostic factor for OS (but not also for DFS) in multivariate analysis. Several other studies demonstrated a negative prognostic impact of low muscle mass on the survival of HNSCC patients [ 14 , 19 , 39 ]. Moreover, despite the statistically significant correlation between FFMI and BMI values measured in individual patients, only FFMI proved to be of significance for predicting OS in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, due to heterogeneity of tumor site, tumor characteristics and tumor stages included in this cohort study, no reliable cutoff value of low SMM for mortality could be provided. Our previous study in patients with HNC treated with curative intent cisplatin-based chemoradiotherapy showed that low SMM at diagnosis is a significant prognostic for decreased survival, changes in SMM after treatment were however not prognostic (32). Further studies are needed to validate the prognostic impact of the cut-off values for low SMM provided in the present study.…”
Section: Discussionmentioning
confidence: 67%
“…The findings concern head and neck cancer, lung cancer as well as other cancer sites. 37 , 38 , 39 , 40 The catabolic effects of chemotherapy probably play a major role here. For example, cisplatin is known to activate nuclear factor kappa‐B cells (NFκB), a key player in inflammation and a trigger for muscle wasting.…”
Section: Discussionmentioning
confidence: 99%